2015
DOI: 10.1152/japplphysiol.00319.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying enhancements in muscle force and power output during maximal cycle ergometer exercise induced by chronic β2-adrenergic stimulation in men

Abstract: The study was a randomized placebo-controlled trial investigating mechanisms by which chronic β2-adrenergic stimulation enhances muscle force and power output during maximal cycle ergometer exercise in young men. Eighteen trained men were assigned to an experimental group [oral terbutaline 5 mg/30 kg body weight (bw) twice daily (TER); n = 9] or a control group [placebo (PLA); n = 9] for a 4-wk intervention. No changes were observed with the intervention in PLA. Isometric muscle force of the quadriceps increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 82 publications
8
80
2
Order By: Relevance
“…This indicates similar detrimental effects on oxidative enzymes as observed in a similar population . In contrast, the content of HAD, an important enzyme in the process of mitochondrial beta‐oxidation, did not change which is in accordance with Hostrup et al who showed that 4 weeks of supratherapeutic terbutaline administration did not affect content of HAD. Collectively, these data indicate that chronic treatment with beta 2 ‐adrenergic agonist may compromise oxidative capacity in skeletal muscle of humans, being consistent with that observed in other species …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This indicates similar detrimental effects on oxidative enzymes as observed in a similar population . In contrast, the content of HAD, an important enzyme in the process of mitochondrial beta‐oxidation, did not change which is in accordance with Hostrup et al who showed that 4 weeks of supratherapeutic terbutaline administration did not affect content of HAD. Collectively, these data indicate that chronic treatment with beta 2 ‐adrenergic agonist may compromise oxidative capacity in skeletal muscle of humans, being consistent with that observed in other species …”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we observed that mean content of electron transport chain complex I‐V of the vastus lateralis muscle declined in response to terbutaline treatment. This observation coincides with the apparent oxidative‐to‐glycolytic muscle phenotypic shift observed after long‐term beta 2 ‐adrenergic agonist treatment in a variety of mammalian species . In addition, long‐term beta 2 ‐adrenergic agonist treatment can cause a transition of myosin heavy chain (MHC) isoform from I to IIa, which may contribute to a reduced oxidative capacity of the skeletal muscle .…”
Section: Discussionsupporting
confidence: 76%
“…The introduction of urinary thresholds and decision limits for salbutamol and formoterol is an innovative way to avoid excessive use by athletes and to lessen the economic burdens associated with therapeutic use exemption applications. However, given that oral ingestion of beta 2 ‐agonists may enhance performance when administered acutely and for a longer duration (Collomp et al., ; van Baak et al., ; Hostrup et al., ; Hostrup et al. , ) and that acute high‐dose inhalation of terbutaline has been shown enhance sprint ability and muscle force (Hostrup et al., ,b; Kalsen et al., ), it is essential to establish a urinary threshold and decision limit for terbutaline.…”
Section: Perspectivesmentioning
confidence: 99%
“…Why should this matter? There is now compelling evidence that terbutaline is performance enhancing, via oral dosing and inhalation 2 4. The exact mechanisms underlying ergogenic actions of β 2 -agonists remain incompletely understood but appear related to β 2 -adrenoreceptor signalling in skeletal muscle by which ion handling and glycolysis are stimulated 1 4.…”
Section: Performance Enhancing Potential Of β2-agonistsmentioning
confidence: 99%
“…Although β 2 -agonists are used to relieve asthma and EIB, high doses have been shown to induce muscle hypertrophy and increase muscle force in mammalian species, including humans 1 2…”
mentioning
confidence: 99%